A review of emergency organisations: the need for a theoretical framework. (16th June 2010) - Hamilton, Andrew; Toh, Keith K.T.
Disaster preparedness in emergency organisations has a heritage born out of civil defence and military traditions, but response to large-scale emergency invariably involves cross-agencies, often involving civilian organisations and resources. Changes to emergency organisations are taking place, and the complexity that has evolved in organisational features is discussed in this paper, drawing upon Victoria, Australia, as an example. Effective command propagation is a critical aspect of emergency response. In attempting to evaluate different models for command and control, this research has identified the requirement for a theoretical framework, which examines the organisation as a whole as well as the intricate relationships throughout the command chain. This paper presents a survey of the research domain as a first step, leading to the need for a theoretical framework for emergency organisations to be developed.